2021
DOI: 10.22190/teme190513081m
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Link Between CSR Reporting and Financial Performance Variables of Belgrade Stock Exchange Companies

Abstract: Corporate Social Responsibility (CSR) reporting has been subject of various discussions of academicians and accounting practitioners. Although the importance of CRS reporting is not under question, the quality of disclosed non-financial information is still under review. In the light of the new Serbian Law on Accounting (Official Gazette of the Republic of Serbia 73/2019) and EU Directive 2014/95 requirements regarding non-financial information, this article investigates the state of non-financial reporting de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Using statistical regression analysis with the level of CSR reporting set as a dependent variable, Rogošić (2014) confirmed that there is a positive correlation between asset value and profits and the CSR reporting levels of banks from Croatia, Bosnia and Herzegovina, and Montenegro. Mijoković et al (2020) examining the companies listed on the Belgrade Stock Exchange come to results which confirm that the financial performance and the size of the company expressed through the value of total assets have a better quality of CSR reporting. They also identify that an audit firm has an impact on CSR reporting, namely companies that select external auditors from the BIG 4 have more information and pay more attention to non-financial corporate responsibility information.…”
Section: Empirical Frameworkmentioning
confidence: 88%
“…Using statistical regression analysis with the level of CSR reporting set as a dependent variable, Rogošić (2014) confirmed that there is a positive correlation between asset value and profits and the CSR reporting levels of banks from Croatia, Bosnia and Herzegovina, and Montenegro. Mijoković et al (2020) examining the companies listed on the Belgrade Stock Exchange come to results which confirm that the financial performance and the size of the company expressed through the value of total assets have a better quality of CSR reporting. They also identify that an audit firm has an impact on CSR reporting, namely companies that select external auditors from the BIG 4 have more information and pay more attention to non-financial corporate responsibility information.…”
Section: Empirical Frameworkmentioning
confidence: 88%
“…Finally, the ProCredit bank displays a positive development of business, but its profitability (ROA 0.44% and ROE 3.89%) is lower compared to the consolidated group results (ROA was recorded to be 0.97%, and ROE was recorded to be 9.7% in 2021). It is important to emphasise that all of the banks in the sample have the relevant ESG data on their websites (more in the methodological part), and that their quality is relevant for further analysis (Mijokovic, Knezevic, & Mizdrakovic, 2020). In terms of environmental loans, three of the banks (Banca Intesa, UniCredit and ProCredit) offer energy effi-ciency loans, while Raiffeisen offers loans for the digitalisation of businesses and the introduction of innovative products (Table 2).…”
Section: Overview Of Sustainable Bankingmentioning
confidence: 99%
“…The current state of development of non-financial reporting is measured using the socially responsible business index of Serbian companies listed on the Belgrade Stock Exchange. Serbian companies, listed as large, have a higher quality of nonfinancial reporting (Mijoković et al, 2021). In the continuation of the paper, we will focus on the disclosure of environmental information within the framework of integrated reporting in the Republic of Serbia, taking into account the results of the mentioned research, including the results reached by Marinković and Stevanović (2022).…”
Section: Introductionmentioning
confidence: 99%